2016
DOI: 10.1111/dom.12667
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of combination therapy with vildagliptin and metformin versus metformin uptitration in Chinese patients with type 2 diabetes inadequately controlled with metformin monotherapy: a randomized, open‐label, prospective study (VISION)

Abstract: VLDM was non-inferior and statistically superior to HDM in glycaemic control in Chinese patients with T2DM inadequately controlled with low-dose metformin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 32 publications
3
13
0
2
Order By: Relevance
“…inhibitor and insulin has been demonstrated in previous studies, the intervention time in those studies was between 24 weeks and 2 years [13][14][15][16][17]. Our results show that the MBG level and the BG level after meals were ameliorated when vildagliptin was added to CSII monotherapy during our short-term treatment period of 7 days, with a significant difference in the MBG manifesting from the third day onwards.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…inhibitor and insulin has been demonstrated in previous studies, the intervention time in those studies was between 24 weeks and 2 years [13][14][15][16][17]. Our results show that the MBG level and the BG level after meals were ameliorated when vildagliptin was added to CSII monotherapy during our short-term treatment period of 7 days, with a significant difference in the MBG manifesting from the third day onwards.…”
Section: Discussionsupporting
confidence: 78%
“…Data are presented as the mean ± standard deviation (SD). MBG refers to the MBG concentration of each day during treatment because pharmacologic action augments the GLP-1 effect [13,23]. Additionally, previous studies have indicated that vildagliptin as addon therapy to various insulin regimens (but not including CSII) can decrease daily insulin doses and improve glycemic control without weight gain [24][25][26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinical trials in Chinese patients with T2DM have shown that metformin can decrease HbA1c by 0.7% to 1.0% . However, no significant difference was observed in glucose control between metformin alone and low‐dose metformin plus DPP‐4 inhibitors . The UKPDS study results showed that metformin also decreased the likelihood of cardiovascular events and death in obese patients with T2DM .…”
Section: Pharmacologic Therapy For Hyperglycaemiamentioning
confidence: 99%
“…In patients already treated with glyburide (glibenclamide), nausea and diarrhoea were more common in those also receiving metformin; these adverse effects were severe in ≤1% and 4% to 5% of patients, respectively . In Chinese patients inadequately controlled with metformin monotherapy who were uptitrated to 1 g twice daily, 4.4% of patients experienced GI AEs …”
Section: Prevalence Of Metformin‐associated Gi Adverse Eventsmentioning
confidence: 99%